Association between Long-Term Exposure to PM2.5 and Lung Imaging Phenotype in CODA Cohort - Youlim Kim (Atmosphere, 2021)
Background and Aims: Ambient particulate matter (PM) is causing respiratory symptoms of individuals at all ages and reducing their lung functions. These individuals could develop chronic pulmonary disease. Recent studies have shown that short-term exposure to PM affects acute exacerbation of respiratory disease. However, evidence about the association between long-term exposure and progression of respiratory diseases remains insufficient. The purpose of this study was to examine the association between long-term exposure of air pollution (PM2.5) and the effect on lung imaging phenotype in dust-exposed Korean adults living near cement factories. Methods: We conducted a cross-sectional analysis on the Chronic Obstructive Pulmonary Disease (COPD) in Dusty Areas (CODA) cohort, which was recruited from 2012 to 2014. Emphysema index and mean wall area were measured using an in-house software program developed by the Korean obstructive lung disease study group based on chest CT scan. A satellite-based model was used to estimate the long-term PM2.5 concentration at each participant’s address. Results: Of 504 eligible participants, 400 participants were analyzed. Their mean age was 71.7 years. Most participants were men (N = 301, 75.3%). The emphysema index of the whole group was 6.63 ± 0.70, and the mean wall area was 68.8 ± 5.2. Image measurement and PM2.5 concentration showed no significant difference in the whole group; however, in the group of subjects with normal lung function, there were significant associations between long-term PM2.5 exposure and emphysema index measurement: 1-year (ß = 0.758, p = 0.021), 3-year (ß = 0.629, p = 0.038), and 5-year (ß = 0.544, p = 0.045). There was no significant association between long-term PM2.5 exposure and mean wall area measurement: 1-year (ß = −0.389, p = 0.832), 3-year (ß = −3.677, p = 0.170), and 5-year (ß = −3.769, p = 0.124). Conclusions: This study suggests that long-term exposure of PM2.5 may affect the emphysematous change in patients with normal lung functions.